2018
DOI: 10.1016/j.neuropsychologia.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of non-dual and focused attention meditations on the formation of automatic perceptual habits in expert practitioners

Abstract: Non-dual meditation aims to undo maladaptive cognitive and affective patterns by recognizing their constructed and transient nature. We previously found high-amplitude spontaneous gamma (25-40 Hz) oscillatory activity during such practice. Nonetheless, it is unclear how this meditation state differs from other practices, in terms of perceptual information processing. Here, we hypothesized that non-dual meditation can downregulate the automatic formation of perceptual habits. To investigate this hypothesis, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 45 publications
5
60
4
1
Order By: Relevance
“…For example, Lutz et al (2004) observed increased gamma oscillatory power and synchrony compared with baseline during non-referential compassion, an open monitoring practice, and this increase was unique to highly experienced practitioners. Recent work has replicated this gamma increase, extending it by showing that gamma power was also higher in open monitoring meditation compared with focused attention meditation (Fucci et al 2018). Increased gamma synchrony may be associated more with a sense of openness, broad awareness, and breaking down of the barriers between self and others (Dahl et al 2015;Josipovic 2014;Lutz et al 2015).…”
Section: Discussionmentioning
confidence: 77%
“…For example, Lutz et al (2004) observed increased gamma oscillatory power and synchrony compared with baseline during non-referential compassion, an open monitoring practice, and this increase was unique to highly experienced practitioners. Recent work has replicated this gamma increase, extending it by showing that gamma power was also higher in open monitoring meditation compared with focused attention meditation (Fucci et al 2018). Increased gamma synchrony may be associated more with a sense of openness, broad awareness, and breaking down of the barriers between self and others (Dahl et al 2015;Josipovic 2014;Lutz et al 2015).…”
Section: Discussionmentioning
confidence: 77%
“…In fact, it ties together in a coherent theoretical scaffold the core meditative notions of attention (top-down deployment of precision weighting), the conditioning power of habitual Self-related patterns of thought and behavior (priors), and the embodied nature of cognition and emotion (interoceptive inference). While this theoretical approach has already been endorsed in a few opinion pieces [9][10][11][12], and is gaining momentum in the community, its application to meditation-related experimental measures is still in its infancy [13]. The present article aims to provide not a detailed FEP-based manifesto for contemplative research ---a task which would require a more formal and extensive effort ---but rather an illustrative example of framing a previously proposed phenomenological model of focused attention (FA) meditation [14] in terms of active inference.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, these approaches can lack ecological validity with regard to the values, principles, and practices of experienced meditators out in the world. Likewise, cross-sectional studies of meditation adepts can offer valuable knowledge about highly experienced RESIDENTIAL MEDITATION RETREATS 4 practitioners [e.g., 18,19], but provide limited information about how this expertise develops or is acquired over time.…”
mentioning
confidence: 99%